PENGARUH KOMPETENSI, PEMANFAATAN TEKNOLOGI INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL TERHADAP KINERJA PEGAWAI (Study Kasus Pada Kantor Dinas Sosial Banda Aceh) - Maksalmina Maksalmina (Jurnal Akuntansi Muhammadiyah (JAM), 2021)
This study aims to determine the effect of competence, use of accounting information technology and internal control on employee performance at Kantor Dinas Sosial Banda Aceh. The population of this study were all employees at Kantor Dinas Sosial Banda Aceh as many as 178 people and the sampling technique used the slovin technique in order to obtain 64 employees. The model used in this study is multiple linear regression analysis. The results of the study show that competence, use of accounting information technology and internal control simultaneously and partially have a significant effect on employee performance at Kantor Dinas Sosial Banda Aceh.